Individual Performance Level Through Self Esteem, Self Efficacy And Locus Of Control In Islamic Perspective - Rifky Widodo; Ersi Sisdianto; Okta Supriyaningsih (UNIVED Press, 2025)
This research aims to analyze the influence of self-esteem, individual efficacy, and locus of control on employee performance at the Regional Development Planning Agency (Bapperida) from an Islamic perspective. It seeks to understand how positive psychological factors contribute to enhancing employee productivity and how Islamic principles can be applied to improve these factors, ultimately impacting work quality. Employing a quantitative approach with a descriptive design, the study focuses on Bapperida employees. Data is collected through a questionnaire assessing the effects of self-esteem, efficacy, locus of control, and performance. The data will be analyzed using regression analysis to test the relationships between variables, along with Smart PLS (Partial Least Squares) to evaluate the structural relationship model and understand the long-term effects of these psychological factors on performance. However, the findings may be influenced by respondents' subjective perceptions, as individual experiences and interpretations of Islamic teachings can affect responses. The study is limited to Bapperida, which may restrict the generalizability of the results to other organizations. Ultimately, the findings indicate that while self-esteem does not positively influence individual performance, both self-efficacy and locus of control have significant positive effects on employee performance.